2018
DOI: 10.1002/ijgo.12559
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐cesarean prophylactic balloon placement in the internal iliac artery to prevent postpartum hemorrhage among women with pernicious placenta previa

Abstract: Pre-cesarean PBP in the internal iliac artery was a safe and effective treatment that could reduce the incidence of both postpartum hemorrhage and hysterectomy among women with pernicious placenta previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
4
15
1
Order By: Relevance
“…In the present study, prophylactic UAE during cesarean delivery was found to be associated with lower total blood loss, units of transfused red blood cells, transfusion of plasma, and incidence of DIC, with no major complications directly attributable to the endovascular procedure. The success rate was similar to that of a previous study of prophylactic balloon placement in the internal iliac artery before cesarean, but higher than that in a study where UAE was performed for emergent management of PPH . The reason for the higher success in the present study may be the preoperative placement of the vessel sheath, which reduces the time taken to achieve embolization.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, prophylactic UAE during cesarean delivery was found to be associated with lower total blood loss, units of transfused red blood cells, transfusion of plasma, and incidence of DIC, with no major complications directly attributable to the endovascular procedure. The success rate was similar to that of a previous study of prophylactic balloon placement in the internal iliac artery before cesarean, but higher than that in a study where UAE was performed for emergent management of PPH . The reason for the higher success in the present study may be the preoperative placement of the vessel sheath, which reduces the time taken to achieve embolization.…”
Section: Discussionsupporting
confidence: 81%
“…Jun et al Stated that pre-cesarean prophylactic balloon placement (PBP) in the internal iliac artery was a safe and effective method that could diminish the frequency of both postpartum haemorrhage and hysterectomy among women with PPP [14]. Hysterectomy rate was 5% in his study which is higher in comparison to our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Hysterectomy rate was 5% in his study which is higher in comparison to our study. Most of the authors mentioned the use of infrarenal abdominal artery balloon occlusion, PBP placement in the internal iliac artery, embolization of the internal iliac or uterine arteries [14] [15] [16]. However, all of these methods have their own drawbacks including sophisticated skilled manpower and advanced setup whereas the conservative suture methods are simple, less time consuming, feasible, can be performed with less skilled manpower and is cost effective [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent popular label used by clinicians reporting on the prenatal diagnosis of PAS has been “morbidly adherent placenta”, which was used in the 19th century to describe placental retention . It has been recently used in WHO's 10th revision of the International Statistical Classification of Diseases (ICD‐10) (http://www.who.int/classifications/icd) and has led to some exotic translation such as “the pernicious placenta” recently used by Chinese authors in both local and international journals . This point also highlights the limited impact of accreta placentation research on the general scientific literature, as leading medical journals are unlikely to publish articles on diseases that do not have universally accepted diagnostic criteria and unequivocal terminology.…”
Section: Diagnosis Of Pasmentioning
confidence: 99%
“…15 It has been recently used in WHO's 10th revision of the International Statistical Classification of Diseases (ICD-10) (www.who.int/classifications/icd) and has led to some exotic translation such as "the pernicious placenta" recently used by Chinese authors in both local and international journals. 16,17 This point also highlights the limited impact of accreta placentation research on the general scientific literature, as leading medical journals are unlikely to publish articles on diseases that do not have universally accepted diagnostic criteria and unequivocal terminology. Each of the other terminologies used so far are suboptimal and exclusive as they do not describe the different grades of PAS-i.e., "adherent", which does not include the invasive grades increta and percreta, and "invasive", which can be confused with gestational trophoblastic disease and, in particular, invasive intrauterine choriocarcinoma.…”
Section: Diagnosis Of Pasmentioning
confidence: 99%